Why does Centralisation fail to internalise Policy Externalities? - Robert A.J. Dur; Hein J. Roelfsema (Tinbergen Institute, 2002)
We provide an explanation why centralisation of political decision makingresults in overspending in some policy domains, whereas too low spending persists in others.We study a model in which delegates from jurisdictions bargain over local public goods provision.If all of the costs of public goods are shared through a common budget, policy makersdelegate bargaining to `public good lovers', resulting in overprovision of public goods. If asufficiently large part of the costs can not be shared, underprovision persists because policymakers delegate bargaining to `conservatives'. We derive financing rules that eliminate theincentives for strategic delegation.
Keywords: D72; D78; H11; H41; 330; Centralised decision making; strategic delegation; financing rules.; Lokale öffentliche Güter; Neue politische Ökonomie; Zentralisierung; Dezentralisierung; Pareto-Optimum; Theorie